Relation between Self-efficacy and Creative Thinking at Writing Skill Learning - Deviana, Ade Destri; Asri, Fauzi; Rusuly, Usfiyatur (Dinamika Ilmu, 2019)
Self-efficacy is a person's belief in his ability to solve planned activities.  Self-efficacy reflects a person’s confidence in their ability to perform tasks creatively and optimistically. The elements to Self-efficacy are mastery experience, vicarious experience, social persuasion, affecative physiological states. Creative thinking is ability to find new ideas originally that are surprising to define it, and also valuable in sensitivity, and the factors are fluency, flexibility, originality, sensitivity, and elaboration. Learning at class need self-efficacy and creative thinking based, the both have relation that influence. Researcher will reveal it at writing skill learning. This study aims at investigating the relationship between self-efficacy and creative thinking of university students at writing skill learning. The method uses quantitative with correlation of two variables with paired sample test. The subject of the study is 53 third semester students of Arabic Language Education Department of Arabic Literature Faculty of State University of Malang Indonesia at writing skill class. Its coefficient correlation is 0,799 and p-value 0,000. The result of this study indicates significant correlation between self-efficacy and creative thinking at writing skill learning. The Fact, self-efficacy increased so creative thinking increased much and otherwise. The Teacher has important role of writing skill learning as facilitator or instructor so that the students like the learning and enhancement of trust.